Fitting fangs in a finite face: A novel fang accommodation strategy in a 280‐million‐year‐old ray‐finned fish. Issue 3 (26th November 2022) - Figueroa, Rodrigo T.; Andrews, James V.
Abstract: Though Paleozoic ray‐finned fishes are considered to be morphologically conservative, we report a novel mode of fang accommodation (i.e., the fitting of fangs inside the jaw) in the Permian actinopterygian † Brazilichthys macrognathus, whereby the teeth of the lower jaw insert into fenestrae of the upper jaw. To better understand how fishes have accommodated lower jaw fangs through geologic time, we synthesize the multitude of ways living and extinct osteichthyans have housed large mandibular dentition. While the precise structure of fang accommodation seen in † Brazilichthys has not been reported in any other osteichthyans, alternate strategies of upper jaw fenestration to fit mandibular fangs are present in some extant ray‐finned fishes—the needlejaws Acestrorhynchus and the gars of the genus Lepisosteus . Notably, out of our survey, only the two aforementioned neopterygians bear upper jaw fenestration for the accommodation of mandibular fangs. We implicate the kinetic jaws of neopterygians in this trend, whereby large mandibular fangs are more easily fit between the multitude of upper jaw and palatal bones. The restricted space available in early osteichthyan jaws may have led to a proliferation of novel ways to accommodate large dentition. We recommend a greater survey of Paleozoic actinopterygian jaw morphology, in light of these results and other recent reevaluations of jaw structure in early fossil ray‐fins. Abstract : Left jaws of † Brazilichthys macrognathus (DGM 1061‐P) in mesial view. Palatoquadrate sectioned to expose the fenestration of the maxilla and the fangs of the lower jaw (in red). Scale bar = 10 mm.